Analysis of The Stability Plan for Kambaniru Weir, East Sumba District - suhudi suhudi; Kiki Frida S; Fifi Damayanti (Journal of Evrímata: Engineering and Physics, 2024)
This research aims to analyze the stability of the Kambaniru Dam which is located in the Luku Kambaniru River, East Sumba Regency, East Nusa Tenggara Province. In this research, a preparatory stage was carried out which included literature study and field observations to collect weir design data and soil mechanics data. The data is then analyzed using an appropriate formula to evaluate the stability of the weir. The results of the data analysis were used to prepare a final report examining the performance of Kambaniru Dam stability planning. The calculation results show that the weir with the planned dimensions, namely 7.00 m high and 69.40 m wide, equipped with a 30 m long energy absorber, meets high safety standards. Stability analysis shows that the safety value (Sf) in terms of overturning force, shear force and soil bearing capacity under normal and flood conditions (with and without an earthquake) exceeds 1.5, indicating that this weir is in a safe condition. Therefore, the construction of the Kambaniru Dam according to the planned dimensions is considered reliable and safe.